2017
DOI: 10.1088/2053-1583/aa8abe
|View full text |Cite
|
Sign up to set email alerts
|

NMR detects molecular interactions of graphene with aromatic and aliphatic hydrocarbons in water

Abstract: IntroductionThe non-covalent interactions between polyaromatic carbon and the hydrocarbon-based structure of organic molecules are both of fundamental interest and a promising means of modifying graphene-based electronics [1][2][3][4][5][6][7], spintronics [8][9][10], optoelectronics and sensors [11][12][13][14]. The high relative surface area of graphene is attractive for the sequestration of xenobiotics in environmental [15][16][17] AbstractPolyaromatic carbon is widely held to be strongly diamagnetic and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 82 publications
(221 reference statements)
0
10
0
Order By: Relevance
“…MALDI (Matrix-Assisted Laser Desorption Ionisation) mass spectra was collected on a Bruker Dal-tonics Ultraflex TOF/TOF mass spectrometer (MA, USA) at the Manchester Interdisciplinary Biocentre, University of Manchester as described earlier ( 34 ). 1 H NMR spectra were recorded using Bruker Avance II+ spectrometers operating at proton frequencies of 400 MHz using BBI 1 H/D-BB Z-GRD Z8202/0347 probe using previously described methods ( 34 , 35 ). The acquired data was processed using Bruker software Topspin 4.0.3.…”
Section: Methodsmentioning
confidence: 99%
“…MALDI (Matrix-Assisted Laser Desorption Ionisation) mass spectra was collected on a Bruker Dal-tonics Ultraflex TOF/TOF mass spectrometer (MA, USA) at the Manchester Interdisciplinary Biocentre, University of Manchester as described earlier ( 34 ). 1 H NMR spectra were recorded using Bruker Avance II+ spectrometers operating at proton frequencies of 400 MHz using BBI 1 H/D-BB Z-GRD Z8202/0347 probe using previously described methods ( 34 , 35 ). The acquired data was processed using Bruker software Topspin 4.0.3.…”
Section: Methodsmentioning
confidence: 99%
“…1 H DOSY experiments (Bichenkova et al, 2017;Valentini et al, 2004) were carried out on the 400 MHz Bruker Avance þ II spectrometer, using 5 mm MIC Z121725/0001DOSY z-diffusion probe with fixed 1 H/X configuration and 2 H lock to generate a gradient strenghth of 30 Gauss/cm/A. The combination of the DIFF30L probe with the 40 Amp gradient current amplifier (GREAT 40) allowed to produce a field strength upto maximum of 1200 Gauss/cm.…”
Section: Analytical Methods and Instrumentationmentioning
confidence: 99%
“…The diffusion coefficient D of the conjugate was measured by 1 H DOSY (Bichenkova et al, 2017;Provencher, 1982aProvencher, , 1982bValentini et al, 2004) from the ratio between the intensity of the attenuated NMR signal I and the initial signal I 0 (as described in the 'Material & Methods' section) using the Stejskal-Tanner equation (Kerssebaum & Salnikov, 2006):…”
Section: Dimer Formationmentioning
confidence: 99%
“…DOSY uses measurements of diffusion to enable the separation of the NMR signals of different components in a mixture, and can be used to probe interactions between components. 36,37 Initially, a standard 1 H spectrum of a graphene dispersion with a BPS concentration of 0.6 mg/mL was collected, shown in Figure 1(c). Figure S4) confirmed that most of the 1 H signal intensity comes from very broad signals.…”
Section: Liquid-phase Exfoliationmentioning
confidence: 99%